RT-PCR Protocols - King, Nicola; O’Connell, Joe.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2002)
RT-PCR, the most widely used technique in biomedical research for analyzing gene expression, has proven a significant boon to the molecular investigation of disease pathogenesis. In RT-PCR Protocols, Joe O'Connell has assembled a panel of highly regarded molecular biologists and clinical researchers to describe in detail their most novel, useful, and interesting RT-PCR applications. Here the newcomer will find readily reproducible protocols for highly sensitive detection and quantification of gene expression, the in situ localization of gene expression in tissue, and the cloning of genes, as well as for analyzing T-cell clones and the differential expression of genes. For the expert seeking to extend the usefulness of RT-PCR, there are user-friendly applications that complement the latest technological advances, including laser-capture microdissection (LCM), real-time and quantitative PCR, microarray technology, cDNA cloning, and antibody engineering. Each protocol emphasizes the technical steps critical for experimental success and includes tips on avoiding potential pitfalls, notes explaining the method's scientific basis and its possible sources of error, and comments on how it might best be accommodated to various experimental circumstances. Diverse and wide-ranging, RT-PCR Protocols offers investigators powerful techniques to be used in the molecular investigation of disease pathogenesis and shows how RT-PCR can complement other technological advances in the design of today's new therapeutic strategies.
RT-PCR in Biomedicine -- The Basics of RT-PCR -- Highly Sensitive Detection and Analysis of mRNA -- Using the Quantitative Competitive RT-PCR Technique to Analyze Minute Amounts of Different mRNAs in Small Tissue Samples -- Detection of mRNA Expression and Alternative Splicing in a Single Cell -- Nested RT-PCR -- Quantitative RT-PCR -- Quantitative RT-PCR -- Rapid Development of a Quantitative-Competitive (qc) RT-PCR Assay Using a Composite Primer Approach -- Quantitation of Gene Expression by RT-PCR and HPLC Analysis of PCR Products -- Time-Resolved Fluorometric Detection of Cytokine mRNAs Amplified by RT-PCR -- Mimic-Based RT-PCR Quantitation of Substance P mRNA in Human Mononuclear Phagocytes and Lymphocytes -- Detection and Analysis of RNA Viruses -- Detection and Quantification of the Hepatitis C Viral Genome -- Semi-Quantitative Detection of Hepatitis C Virus RNA by “Real-Time” RT-PCR -- RT-PCR for the Assessment of Genetically Heterogenous Populations of the Hepatitis C Virus -- In Situ Localization of mRNA Expression -- in situ Immuno-PCR -- RT-PCR from Laser-Capture Microdissected Samples -- Mycobacterium paratuberculosis Detected by Nested PCR in Intestinal Granulomas Isolated by LCM in Cases of Crohn’s Disease -- RT-PCR-Based Approaches to Generate Probes for mRNA Detection by In Situ Hybridization -- Differential mRNA Expression -- Amplified RNA for Gene Array Hybridizations -- Semi-Quantitative Determination of Differential Gene Expression in Primary Tumors and Matched Metastases by RT-PCR -- Genetic Analysis -- Detection of Single Nucleotide Polymorphisms Using a Non-Isotopic RNase Cleavage Assay -- RT-PCR in Immunology -- Detection of Clonally Expanded T-Cells by RT-PCR-SSCP and Nucleotide Sequencing of T-Cell Receptor ?-CDR3 Regions -- Generation of scFv from a Phage Display Mini-Library Derived from Tumor-Infiltrating B-Cells -- Generation of Murine scFv Intrabodies from B-Cell Hybridomas -- Quantitation of mRNA Levels by RT-PCR in Cells Purified by FACS -- RT-PCR in Anti-Sense Technology -- Detection of Anti-Sense RNA Transcripts by Anti-Sense RT-PCR -- RT-PCR in cDNA Cloning -- RT-PCR in cDNA Library Construction -- An RT-PCR-Based Protocol for the Rapid Generation of Large, Representative cDNA Libraries for Expression Screening.
Keywords: Cell biology; Cell Biology